Community of small mammals along an elevational gradient in Biological Reserve of Serra do Japi, municipality of Jundiaí‐SP, Brazil. (11th July 2019) - Sakane, Karina Koibuchi; Percequillo, Alexandre Reis; Setz, Eleonore Zulnara Freire
Abstract: Studies of elevational gradients in forests are particularly interesting for the considerable differences that can be observed over short distances, such as in vegetation and temperature. Different taxonomic groups display varying types of distribution patterns along elevational gradients, with unimodal distribution being recognised as the most common pattern. The distribution of species can be affected by a range of factors that include, biotic, spatial, climatic, historic and energetic. Small mammals represent an ideal model for studies about distribution and habitat use as they can be highly abundant, tend to have different diets and use space differently. The aims of this study are to build a comprehensive understanding of the community of small mammals of the Biological Reserve of Serra do Japi and to explore its distribution pattern along elevational gradients. We investigated the influence of biomass of arthropods, fruits and seeds and percentage of ground cover, canopy cover and vertical vegetation at richness and abundance of small mammals at three different elevations. To accomplish this, we used seventy‐two pitfall traps of 63 L to capture small mammals and distributed them equally across three elevations defined as low (880–899 m), intermediate (1046–1089 m) and high (1170–1189 m). Each elevation had three lines or replicas of traps. Throughout the study, we captured one hundred and fourteen individuals belonging to eleven species of small mammals. The presence of rare and endemic species demonstrates the importance of conservation and maintenance of the Biological Reserve of Serra do Japi. In regard to the distribution of species, despite the short gradient range, we found a unimodal pattern and a positive correlation between ground cover (fallen twigs and branches up to 1 m high) and richness and abundance of small mammals. More ground cover can reduce the effects of competition and predation on small mammals' communities. Abstract in Portuguese is available with online material. Resumo: Estudos ao longo de gradientes altitudinais são interessantes devido a presença de diferenças nítidas em curtas distâncias, por exemplo, da vegetação e temperatura. Diferentes grupos taxonômicos apresentam uma variedade de padrões de distribuição ao longo de gradientes altitudinais. O padrão de distribuição unimodal é reconhecido como o mais comum dentre eles. A distribuição de espécies é influenciada por fatores bióticos, espaciais, climáticos, históricos e energéticos. Os pequenos mamíferos são bons modelos para estudos sobre distribuição e uso de habitat pois apresentam elevada abundância, diferentes dietas e utilizam o espaço de diferentes formas. Os objetivos deste estudo incluem conhecer a comunidade de pequenos mamíferos da Reserva Biológica da Serra do Japi e explorar o padrão de distribuição ao longo do gradiente altitudinal. Nós investigamos a influência da biomassa de artrópodes, frutos e sementes e a influência da porcentagem de cobertura do solo, cobertura do dossel e vegetação vertical na riqueza e abundância de pequenos mamíferos em três diferentes altitudes. Para isso, utilizamos 72 armadilhas de interceptação e queda de 63 litros para a captura de pequenos mamíferos e as distribuímos igualmente em três altitudes definidas como baixa (880‐899 m), média (1046‐1089 m) e elevada (1170‐1189 m). Em cada altitude instalamos três linhas/réplicas de armadilhas. Ao longo do estudo capturamos 114 indivíduos de 11 espécies de pequenos mamíferos. A presença de espécies raras e endêmicas demonstra a importância da conservação e da manutenção da Reserva Biológica da Serra do Japi. Em relação a distribuição das espécies, apesar do gradiente altitudinal curto, encontramos um padrão de distribuição unimodal e uma correlação positiva entre cobertura do solo (galhos caídos e ramos de até um metro de altura) e riqueza e abundância de pequenos mamíferos. A maior cobertura do solo pode amenizar os efeitos da competição e da predação nas comunidades de pequenos mamíferos.